IMPROVING STUDENTS’ ABILITY IN EXPRESSING IDEAS IN DESCRIPTIVE WRITING BY USING PICTURE SERIES TECHNIQUE (A Quasi – Experimental Research at SMPN 14 Bengkulu City) - Leny Susiana (JOALL (Journal of Applied Linguistics and Literature), 2016)
This research investigated the effect of picture series technique to develop the students’ ability in expressing ideas in descriptive writing. It was a quasi – experimental research that involved two classes of samples, they are experimental class and control class. The population consisted of the second year students’ of Junior High School Number 14 Bengkulu in Academic Year 2008/2009. The experimental class was treated by picture series technique for one month, while the control class was taught by using the conventional technique. Both classes were given pre test before treatment. The average score of both classes were analyzed by using the t -test formula. T count was smaller than t table (0.126<2.000). It means that there was no significance difference between the experimental and the control class. In other words, those classes could be accepted as the samples for this research. Both classes were given a post test after them giving a treatment (by using picture series technique) for several times. The average scores both classes were calculated by using the t-test formula. T obtained was higher than t-table (4.054>2.000). The result showed that there was a significant difference in post test score average between the experimental class and the control class. It means that picture series technique could improve the Junior High School Students’ ability in expressing ideas in descriptive writing.